Inhibiting TLR7 Expression in the Retinal Pigment Epithelium Suppresses Experimental Autoimmune Uveitis - Lo, Sheng-Min; Hwang, Yih-Shiou; Liu, Chao-Lin; Shen, Chia-Ning; Hong, Wei-Hsin; Yang, Wei-Cheng; Lee, Meng-Hua; Shen, Chia-Rui (Frontiers in Immunology, 2022)
Experimental autoimmune uveitis (EAU), a model of human uveitis, is an organ-specific, T cell-mediated autoimmune disease. Autoreactive T cells can penetrate the blood-retinal barrier, which is a physical defense composed of tight junction-linked retinal pigment epithelial (RPE) cells. RPE cells serve as antigen-presenting cells (APCs) in the eye since they express MHC class I and II and Toll-like receptors (TLRs). Although previous studies have shown that supplementation with TLR agonists exacerbates uveitis, little is known about how TLR signaling in the RPE contributes to the development of uveitis. In this study, we isolated the RPE from EAU mice, which were induced by active immunization (aEAU) or adoptive transfer of antigen-specific T cells (tEAU). The expression of TLRs on RPE was determined, and both aEAU and tEAU mice exhibited induced tlr7 expression. The TLR7 agonist R848 was shown to induce aggressive disease progression, along with significantly elevated levels of the uveopathogenic cytokine IL-17. Furthermore, not only IL-17 but also R848 appeared to enhance the inflammatory response and to impair the barrier function of the RPE, indicating that TLR7 signaling is involved in the pathogenesis of EAU by affecting the behaviors of the RPE and consequently allowing the infiltration of autoreactive T cells intraocularly. Finally, local application of shRNA against TLR7 delivered by recombinant AAV effectively inhibited disease severity and reduced IFN-γ and IL-17. Our findings highlight an immunomodulatory role of RPE TLR7 in EAU development and provide a potential therapeutic strategy for autoimmune uveitis.